Novel And Convenient Synthesis of 1,4-Dihydro Pyridines - Rao, V.S.; Arun Kumar Gupta, S.V.S.; giridhar N. Jai Ganesh, P.; Reddy, B.S. (Asian Journal of Chemistry, 2010)
Some novel 1,4-dihyropyridine fused/spiro systems were synthesized by the reaction of different types of α, β -unsaturated carbonyl/nitriles with 2,4-thiazolidinedione in the presence of excess of ammonium acetate at reflux condition. The structure of the compounds were assgined by spectral and elemental data.